The Pechenegs Nomads in the Political and Cultural Landscape of Medieval Europe - Paroń, Aleksander (East Central and Eastern Europe in the Middle Ages, 450-1450, 2021)
In The Pechenegs: Nomads in the Political and Cultural Landscape of Medieval Europe, Aleksander Paroń offers a reflection on the history of the Pechenegs, a nomadic people which came to control the Black Sea steppe by the end of the ninth century. Nomadic peoples have often been presented in European historiography as aggressors and destroyers whose appearance led to only chaotic decline and economic stagnation. Making use of historical and archaeological sources along with abundant comparative material, Aleksander Paroń offers here a multifaceted and cogent image of the nomads' relations with neighboring political and cultural communities in the tenth and eleventh centuries. Readership: All those who are interested in the history of medieval nomadic peoples in Europe, and anyone seeking to understand the relations of nomads of the late pre-Mongol epoch with the outside world.